(3GdYOGdI GdJUGdMjI aj GdSjGSI GdLfGFjI (B:s (3OQGSI ebGQfI (B: (3GdUdM GdLfGFj(B-(3GdhSGWI GdLfGFjI(B-(3GdJShjI GdLfGFjI(B-(3GdeaGhVI Ydi GdGYJQGa (B/s - (3Hfj Wg, eMeO SdGeIs ((3YeGf, GdCQOf (B:s (3OGQ GdMGeO ddfTQ hGdJhRjY,s, 2019)
(3jJMOK GdcJGH Yf GdYOGdI GdJUGdMjI aj GdSjGSI GdLfGFjI MjK Cf TgOJ GdYOGdI GdLfGFjI JWhQGJ edMhXI aj GdSfhGJ GdCNjQI aj eNJda HQGeLgG hGdjGJ YedgG hbWYJ GdOhd GdeJbOeI ThWG aj HfGA fXe YUQjI dgG ef MjK JTQjYGJgG hCLgRJgG hGdJRGegG HGdeHGOF hGdeYGjjQ GdOhdjI hYdi GdQZe ef Pdc abO CXgQJ GdGJLGgGJ GdMOjKI ddYOGdI GdLfGFjI VQhQI GdGfJbGd Edi eaGgje GdYOGdI GdJUGdMjI aj NWW hSjGSI GdeTQY GdLfGFj HGYJHGQ Cf gPg GdeaGgje JTcd CSdhHG eSJMOKG aj EOGQI GdOYhi GdLfGFjI NGUI HYO Cf KHJ YOe bOQI efXheI GdYOGdI GdLfGFjI GdJbdjOjI Ydi ehGLgI GdLQjeI hGdMO ef BKGQgG(B.s
(3HHdjhLQGajI (B: (3UaMI (B451-459 s
Keywords: (3GdUdM (B((3bGfhf LfGFj(B)s -- (3GdCQOfs; (3bGfhf GdELQGAGJ GdLfGFjIs -- (3GdCQOfs; (3GdYOGdI GdJUGdMjIs -- (3GdCQOfs